2004
DOI: 10.1016/j.femsim.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Human salivary aggregation inStreptococcus intermediustype g strains: relationship with IgA

Abstract: Bacterial aggregation is an important step in elimination from the human body to protect against infection. Streptococcus intermedius K1K aggregates in human saliva. In this study, the salivary agglutinin was identified. The aggregation level was very strong in sonic-treated saliva and 1-microm filtrate. Preincubation of human saliva with anti-human alpha chain serum or anti-human whole saliva serum completely inhibited aggregation, but preincubation with anti-human micro chain serum or anti-Fc fragment of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Considered to be a process that promotes the clearance of bacteria from the oral cavity (22), bacterial aggregation has been widely studied and different assays have been developed to determine the aggregation of oral bacteria by human saliva (15). In addition to aggregation of bacteria by human whole saliva, the effect of different components of human saliva on the aggregation of oral bacteria has also been explored (4, 18, 19, 31). However, less is known about the effects of the saliva of other species that are often used in laboratory animal models, such as mice, on bacterial aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered to be a process that promotes the clearance of bacteria from the oral cavity (22), bacterial aggregation has been widely studied and different assays have been developed to determine the aggregation of oral bacteria by human saliva (15). In addition to aggregation of bacteria by human whole saliva, the effect of different components of human saliva on the aggregation of oral bacteria has also been explored (4, 18, 19, 31). However, less is known about the effects of the saliva of other species that are often used in laboratory animal models, such as mice, on bacterial aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in aggregation of bacteria by saliva from mPIP −/− compared with WT mice may be attributed to the absence of PIP from the saliva of mPIP −/− mice. However, the role of mPIP in the aggregation of bacteria by mouse saliva has not been defined and saliva contains other carbohydrates and proteins that bind to oral streptococci and may also promote aggregation (18–20, 27, 31). Murine PIP could play a direct role or an ancillary role to these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of bacterial aggregates has generally been reported as a response to infection, and a variety of factors mediate the induction of aggregation (Secor et al, 2018; Cai, 2020). In humans, for example, interactions between IgA secreted in saliva and bacterial surface components induce aggregation to promote clearance by blocking bacterial adhesion to oral tissue surfaces (Yamaguchi, 2004). Similarly, mucus secreted by the colon induces the aggregation of intestinal bacteria, preventing inflammation (Bergström et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while the first description of the biofilm concept came from Leeuwenhoek examining his own scraped-off dental plaque (Høiby, 2017), saliva has been reported to facilitate the aggregation of bacteria from a number of different genera, including species such as Actinomyces israelii, Actinomyces naeslundii, Actinomyces viscosus, Bacteroides intermedius, Bacteroides gingivalis, Streptococcus cricetus, Streptococcus mutans, Streptococcus rattus, Streptococcus sanguis, Streptococcus sobrinus, Streptococcus intermedius, Streptococcus gordoni (Rosan et al, 1982;Golub et al, 1985;Koop et al, 1989;Yamaguchi, 2004;Kitada and Oho, 2012;Itzek et al, 2017). It was suggested that the interactions between salivary IgA and bacterial surface components cause bacterial aggregation, which also depends on various factors (Koop et al, 1989;Yamaguchi, 2004). As a result, saliva blocks the adherence of bacteria onto surfaces and promotes the clearance from the oral cavity.…”
Section: Other Body Fluidsmentioning
confidence: 99%